The 'creation' of a tourist destination: A success Story or a 'generic' place? The case of Dubai - Christos Liouris; Alex Deffner (European Regional Science Association (ERSA), 2010)
The relatively short social and economic history of the urban Gulf has undergone radical evolutions over recent years. Cities in the Gulf have advanced on investing in holistic urban planning and branding strategies. The majority of these investments were not merely intent on supplying various infrastructures for local communities, but more importantly aimed at foreign influx, through tourism and attracting foreign businesses with the possibility to set-up regional offices and increase revenues. Important in this is both the hardware (city planning) and software (city marketing). In recent years, major cities - such as Dubai, Abu Dhabi and Doha - have been confronted with providing a strong and profitable infrastructure for their respective tourist/business industries. This brings to light some new dilemmas to be answered, which include the following: 1. Space vs. time 2. Short term vs. long term 3. Planning vs. marketing 4. Infrastructure vs. network 5. Global vs. local ,Üí glocal 6. Work vs. leisure 7. Economy vs. culture & society 8. Traditional marketing vs. alternative marketing The paper then discusses the new approaches linking city planning with city marketing, like time planning, leisure (cultural, tourism, sports, entertainment) planning, social town planning (incorporating the previous two), creative cities, urban regeneration, strategic planning, collaborative planning, urban management, Public Private Partnerships and the representation of the city in cinema. Then an attempt is made to answer questions like the influence that the temporary nature of many of the residents/expats of the Gulf cities have on their future composition, the social implications of the rapid economic growth, the kind of projects that are revealed when considering the reassessment of the social/economic infrastructure within these cities etc., before ending with the conclusions about the necessity of a strategic urban development plan especially for cities with a strong infrastructure for tourism & business, incorporating: City marketing plan involving the cooperation of tourists, businesses & residents (focus on the quest for local identity) Leisure plan (combining tourism, culture, sports & entertainment) Time master plan
Keywords: 330; Gulf Region; tourism; city marketing; city planning; leisure